Flashpoint. - Bickers, Charles (Far Eastern Economic Review, 2000)
Pointless animation on the Internet appears to have become the norm as new Internet-creativity tools become widely available. Music and moving pictures can add much to a website, but lax control over creative departments means that getting information from a website is becoming increasingly difficult. Sites that rely on online sales generally recognize that there is no point using flashy animation when a simpler option will suffice.